Is Your Health Data Safe with AI Systems? A Professional and Academic Perspective - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The integration of Artificial Intelligence AI into healthcare promises a revolution in diagnostics, personalized medicine, and drug discovery. From analyzing...
Keywords: Drug Discovery; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care